THEORETICAL AND PRACTICAL FOUNDATIONS OF VISUALIZING TEXTUAL INFORMATION BASED ON GENERATIVE ARTIFICIAL INTELLIGENCE TECHNOLOGIES - Qunnazarov, Amangeldi Quatbayevich (SCIENCE and SOCIETY, 2026)
This article provides an overview of the role, theoretical foundations, and practical possibilities of generative artificial intelligence technologies in visualizing text information. Furthermore, the capabilities of ChatGPT, Gemini, Claude, Midjourney, Canva AI, Napkin AI, and other modern generative artificial intelligence services in creating images, infographics, and diagrams from text will be explored.
Keywords: generative artificial intelligence; text information; visualization; infographics; educational technologies; Napkin AI; ChatGPT; Midjourney; Canva AI